Modelling the demand for life insurance in Malaysia - Lim, Chee Chee (Universiti Utara Malaysia, 2012)
This study is undertaken to better understand the relationship between life insurance demand and macroeconomic factors by cointegration analysis and ordinary least squares (OLS) estimation. The major findings of this study show that there is no equilibrium (long-term) relationship between life insurance demand (in terms of new sum insured, new annual premium, sum insured in force and annual premium in force) and the macroeconomic factors, namely GDP per capita, the discount rate of Treasury Bill, inflation and the level of financial development. However, inflation is found to be significantly positively associated with life insurance demand by new sum insured.The latter finding possibly suggests that Malaysians tend to purchase a bigger amount (nominal value) of life insurance as a bequeath to their beneficiaries in an inflationary environment in order to maintain their purchasing power for the untimely death of the insured persons.